Technical solutions to improve the management of non‐muscle‐invasive transitional cell carcinoma: summary of a European Association of Urology Section for Uro‐Technology (ESUT) and Section for Uro‐Oncology (ESOU) expert meeting and current and future perspectives - Bach, Thorsten; Rassweiler, Jens (BJU international, 2015)
The aim of the present review was to compare state‐of‐the‐art care and future perspectives for the detection and treatment of non‐muscle‐invasive transitional cell carcinoma (TCC) of the bladder. We provide a summary of the third expert meeting on ‘Optimising the management of non‐muscle‐invasive bladder cancer, organized by the European Association of Urology Section for Uro‐Technology (ESUT) in collaboration with the Section for Uro‐Oncology (ESOU), including a systematic literature review. The article includes a detailed discussion on the current and future perspectives for TCC, including photodynamic diagnosis, optical coherence tomography, narrow band imaging, the Storz Professional Image Enhancement system, magnification and high definition techniques. We also provide a detailed discussion of future surgical treatment options, including en bloc resection and tumour enucleation. Intensive research has been conducted to improve tumour detection and there are promising future perspectives, that require proven clinical efficacy. En bloc resection of bladder tumours may be advantageous, but is currently considered to be experimental.
Gesehen am 28.03.2018